Synthesis and Crystal Structure of Complex (μ-S2)Fe2(CO)4(PPh3)2 - Gao, Wei; Yuan Jing Yang, Juan (Asian Journal of Chemistry, 2013)
The title complex (μ-S2)Fe2(CO)4(PPh3)2 was prepared by reaction of (μ-S2)Fe2(CO)6 and PPh3 at reflux in toluene. Its structure was determined by single crystal X-ray diffraction analysis. The crystals are monoclinic, space group C2/c with a = 19.203(7), b = 10.199(3), c = 19.403(7) Å, a = 90.00, b = 102.386(5), g = 90.00º, V = 3712(2) Å3, Z = 4, F(000) = 1664, Dc = 1.454 g/cm3, μ = 1.021 cm-1, the final R = 0.0395 and wR = 0.0944. A total of 18901 reflections were collected, of which 4437 were independent (Rint = 0.0545).